ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP TINGKAT KEPUASAN PESERTA ASKES MELALUI PENDEKATAN DIMENSI SERVQUAL - Djoko Setyo Hartono (Value Added : Majalah Ekonomi dan Bisnis, 2007)
Recently healty insurance as insurance instrument as well as a basic need for modern society want. Hardly competition in this business, so decision maker have to do right policy on marketing strategy and create new product to fullfilled customers satisfaction. This research is a study about relationship between service quality and the customers’ satisfaction. Some researcher already doing the survey about the influence of service quality and trust to the customers’ satisfaction. While this research want to prove researchers’ hypothesis about the influence of service quality and the customers’ satisfaction with ASKES in Kabupaten Semarang, Ungaran City. Number of sample taken which is 100 respondents of healty insurance user is using purposive sampling tehnique, only respondents that could found in questionaire distribution area will representate population of ASKES users in Ungaran Hospital and Ambarawa Hospital. The analysis using in the data processing which operated through the SPSS program. The Research result shows that the most influenced variable significantly to the customers’ satisfaction is trust that company will give the right information, customers’ trust that company will apply to the customers’ complaint and customers’ trust that company will keep their promises as the indicator. Nevertheless service quality also has a signifikan influence to the customers’ satisfaction. Final conclusion of this research is that service quality have significant influence to the customers’ satisfaction. With this satisfaction, customers will automatically keep their transaction regularly, and recommendize product quality performance to other people.